Time-temperature behavior of carbon/epoxy laminates under creep loading - Ornaghi Jr, Heitor L. [UNESP]; Almeida, Jose Humberto S.; Monticeli, Francisco M. [UNESP]; Neves, Roberta M.; Cioffi, Maria Odila H. [UNESP] (Springer, 2020)
The time-temperature creep behavior of advanced composite laminates is herein determined through a comprehensive set of experiments and analytical modeling. A complete structureversusproperty relationship is determined through a wide range of temperature and applied stress levels at the three states of the composite: glassy, glass transition, and rubbery regions. Weibull, Eyring, Burger, and Findley models are employed to predict the experimental data and to better elucidate the material behavior. Experimental creep tests are carried out under ten min and two days aiming at calibrating fitting parameters, which are essential to validate short-term creep tests. The Weibull and Eyring models are more suitable for determining the time-temperature superposition (TTS) creep response in comparison to the Burger and Findley models.
Keywords: Advanced composites; Viscoelasticity; Creep; Time-temperature superposition